Implementasi Prinsip Keadilan Syariah dalam Proses Promosi dan Pengembangan Karier Karyawan di BMT Beringharjo Cabang Ponorogo - Fadhil Wafa; Aji Damanuri (Indo Publishing, 2025)
This study aims to examine in depth the implementation of the principle of sharia justice ('adl) in the promotion and career development process of employees at BMT Beringharjo, Ponorogo Branch, as a sharia microfinance institution that plays a strategic role in strengthening the people's economy. The principle of justice in Islam is not only understood as formal equality, but also includes substantive justice that protects the rights, potential, and dignity of human resources. In the context of human resource management, the application of sharia justice functions as a moral and managerial instrument to ensure that the promotion and career development process is carried out objectively, proportionally, and oriented towards the values of trust and professionalism. This study begins with the phenomenon of a perception gap between the institution's promotion policy and employee expectations based on religious values, where the implementation of the principle of justice often clashes with the demands of efficiency and internal competition of the institution. This study uses a qualitative approach with a descriptive-analytical method, where data were obtained through in-depth interviews, participant observation, and a review of HR policy documents at BMT Beringharjo, Ponorogo Branch. The results show that the institution has attempted to internalize the values of sharia justice through promotion policies based on performance, loyalty, and work integrity. However, field practice shows that the implementation of these principles still faces obstacles in the aspect of transparency of assessment and policy communication between organizational levels. In the context of maqashid sharia, the results of this study emphasize the importance of integrating spiritual, moral, and professional values in the career management system to create a balance between organizational performance achievement and human resource welfare. These findings are expected to provide theoretical contributions to the development of a sharia justice-based HR management model and serve as a practical reference for sharia microfinance institutions in building a promotion and career system that is fair, sustainable, and based on Islamic values.